Proposal for a public management model applied to the municipal government of Lurigancho (Chosica), Lima, Peru - Noel Espinoza, Arturo Juan (2022)
The main objective of this research is to establish the relationship between the non-existence of sustainable development in the district of Lurigancho (Chosica) and the lack of a management model that encourages adequate public policies. For which, a citizen survey was carried out, the result of which was analyzed; Likewise, pertinent documentary information was reviewed. The investigation was carried out on the basis of a diagnosis whose time limit is 2020; identifying ineffectiveness in the situational diagnosis and planning system, in closing gaps in services to citizens, in the evaluation and monitoring of results, and in the continuous improvement of administrative systems and attention to citizens. A series of theoretical aspects related to public management, municipal management and sustainable development were addressed. Finally, a proposal for a management model for local governments is presented, taking as a reference the situation of the district of Lurigancho (Chosica).